Increasing the use of multimodal analgesia during adult surgery in a tertiary academic anaesthesia department - Andrea V Olmos; Sasha Steen; Christy K Boscardin; Joyce M Chang; Genevieve Manahan; Anthony R Little; Man-Cheung Lee; Linda L Liu (BMJ Open Quality)
Objective Multimodal analgesia pathways have been shown to reduce opioid use and side effects in surgical patients. A quality improvement initiative was implemented to increase the use of multimodal analgesia in adult patients presenting for general anaesthesia at an academic tertiary care centre. The aim of this study was to increase adoption of a perioperative multimodal analgesia protocol across a broad population of surgical patients. The use of multimodal analgesia was tracked as a process metric. Our primary outcome was opioid use normalised to oral morphine equivalents (OME) intraoperatively, in the postanaesthesia care unit (PACU), and 48 hours postoperatively. Pain scores and use of antiemetics were measured as balancing metrics.Methods We conducted a quality improvement study of a multimodal analgesia protocol implemented for adult (≥18 and≤70) non-transplant patients undergoing general anaesthesia (≥180 min). Components of multimodal analgesia were defined as (1) preoperative analgesic medication (acetaminophen, celecoxib, diclofenac, gabapentin), (2) regional anaesthesia (peripheral nerve block or catheter, epidural catheter or spinal) or (3) intraoperative analgesic medication (ketamine, ketorolac, lidocaine infusion, magnesium, acetaminophen, dexamethasone ≥8 mg, dexmedetomidine). We compared opioid use, pain scores and antiemetic use for patients 1 year before (baseline group—1 July 2018 to 30 June 2019) and 1 year after (implementation group—1 July 2019 to 30 June 2020) project implementation.Results Use of multimodal analgesia improved from 53.9% in the baseline group to 67.5% in the implementation group (p<0.001). There was no significant difference in intraoperative OME use before and after implementation (β0=44.0, β2=0.52, p=0.875). OME decreased after the project implementation in the PACU (β0=34.4, β2=−3.88, p<0.001) and 48 hours postoperatively (β0=184.9, β2=−22.59, p<0.001), while pain scores during those time points were similar.Conclusion A perioperative pragmatic multimodal analgesic intervention was associated with reduced OME use in the PACU and 48 hours postoperatively.